Applications of Artificial Intelligence in IT Marketing and Barriers to Adoption - Vahia, Shishir (Digital Repository of Theses - SSBM Geneva, 2025)
Applications of Artificial Intelligence (AI) in IT marketing have been advancing at a fast pace and AI technologies are evolving. This research aims to investigate the challenges of adoption of AI in IT marketing, explore strategies for addressing these challenges and identify future scope of research in this field.